The clinical features and outcomes of diabetes patients infected with COVID-19: a systematic review and meta-analysis comprising 192,693 patients - Kai Liu; Shu Liu; Ting-ting Xu; Hong Qiao (Frontiers in Medicine)
ObjectivesWe sought to explore the relevance of analyses that include critical laboratory parameters and drug treatment, clinical characteristics of diabetic patients who are infected with COVID-19, to the development of individualized treatment strategies for diabetic patients infected with COVID-19.MethodsWe searched Cochrane, Embase, FMRS, Pubmed, Springer, Web of Science databases for systematic reviews and meta-analyses to estimate the clinical characteristics and prognosis of confirmed covid-19 infections in patients with and without diabetes.ResultsOur meta-analysis included a total of 32 studies with 192,693 COVID-19 patients. Common comorbidities in the diabetic group were hypertension, cerebrovascular disease, chronic kidney disease and cardiovascular disease. We discovered that white blood cell count, neutrophil count, inflammatory marker levels, D-dimer, urea, precursor of the brain natriuretic peptide (Pro-BNP) increased and lymphocyte count, estimated glomerular filtration rate (eGFR), albumin decreased significantly in the diabetic group in laboratory test results. Compared with the non-diabetic group, the diabetic group had a higher incidence of complications in acute respiratory distress syndrome (ARDS), shock, acute heart injury, acute kidney injury and more regularly used oxygen therapy, invasive ventilation, non-invasive ventilation, continuous renal replacement therapy (CRRT), extracorporeal membrane oxygenation (ECMO) treatment. Mortality and intensive care unit (ICU) hospitalization rates were highest in the diabetic group than in the non-diabetic group (p < 0.05).ConclusionDiabetic patients hospitalized with COVID-19 have an increased risk of death, lower discharge rates, and higher ICU admission rates. Their presence of hypertension, cerebrovascular disease, chronic kidney disease (CKD), higher levels of inflammatory markers. Multiple complications are all predictors of poor outcomes in people with diabetes. Our findings will help identify elevated risk factors in diabetics, which will benefit early prediction.